Engineering properties of high volume slag cement grout in tropical climate - Hussin, Mohd. Warid; Lim, Siong Kang; Zakaria, Fadhadli (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 2007)

(untitled)
Concrete repair is a complex process. It must successfully integrate new material with the old one to form a lasting composite that can withstand harsh environment. Cement based grout is used for most general repair works due to its low cost and availability. This research, however, used ordinary Portland cement and ground granulated blast furnace slag (GGBFS) as binders to produce a slag cement based grout. The research objective is to produce a sufficient mix proportion for slag cement based grout that has good engineering properties and can be used as concrete repair material in tropical climates. Flow cone test was used to determine the mix proportions of cement grout. Several batches of 50% slag replacement cement mixes were designed and tested for its flowability and compressive strength properties. Finally, the mix proportion with fresh properties, namely workability, bleeding, and setting time that fulfill the requirements of ASTM C 937 and has optimum strength development was selected. The optimum compressive strength obtained for 50% slag replacement cement grout was above 30 MPa and its flexural strength was above 9 MPa under water curing condition. Result of drying shrinkage test strengthened the finding that the replacement of 50% slag as binder to cement mix with proper mix proportion is suitable to be used in normal grade concrete repairs under tropical climate.